Economic Rationality and Health Behavior: Investigating the Link Between Financial Literacy and the BMI - Kota Ogura; Honoka Nabeshima; Tomoka Kiba; Sakiho Aizawa; Hibiki Nagahama; Haruka Izumi; Mostafa Saidur Rahim Khan; Yoshihiko Kadoya (Behavioral Sciences)
Obesity is a major global health concern related to chronic diseases and rising healthcare costs. While previous studies focused on diet habits, environmental issues, and physical activity, financial literacy remains an overlooked factor in weight management. This study examined the relationship between financial literacy and the body mass index (BMI), using financial literacy as a proxy for rational health decision-making. A quantitative approach was employed, where linear regression analyzed the BMI as a continuous variable and a probit regression assessed overweight, normal weight, and underweight categories. A nationwide survey, the Preference Parameter Study, conducted by Osaka University, Japan, in the United States, provided the data for this study. The results indicate a significant negative association between financial literacy and the BMI, with higher financial literacy linked to a lower BMI and a greater likelihood of maintaining a normal weight. The key control variables, including impatience, gender, education, income, and smoking, also significantly affected the BMI. These findings reflect a strong correlation between financial literacy and the weight status; however, due to data limitations, causal inferences could not be made. We acknowledge the potential endogeneity and the cross-sectional nature of the data as limitations. Thus, while our results suggest a potential role for financial literacy in promoting rational health behavior, the policy implications should be interpreted with caution. Future research should explore targeted interventions across various demographic groups to maximize the impact.